The Cognitive, Affective, and Psychomotor Domain on English Lesson Plan in School Based Curriculum - Irma Handayani; Mukhaiyar Mukhaiyar; Hermawati Syarif (International Journal of Multidisciplinary Research of Higher Education, 2018)
This research is focus to analyze teachers in implementing three domains that is cognitive, affective, and psychomotor that suggested by Bloom. Then problems that feced by teachers in implementing these three domian in teaching and learning process. this is qualitative research in case study approach. Data of this research were get from observation and interview three teachers whose teach English subject in Senior High School 5 Padang West Sumatra Indonesia. Base on data that researcher have got, researcher found that: first teachers are not well prepare lesson plan. This is seen in cognitive domain (36.6%) then affective (27.6%) and psychomotor (35.7%). In general from percentage above, result of education still not maximal. Second, there are three problems that faced by teachers in teaching and learning proces, they are: (i) limit of time implementing three domain, (ii) ability of each students in english subject and (iii) limitation of teachers in understanding in implementing this currriculum because of lack training.